Clinical characteristics and outcomes of ocular adnexal mantle cell lymphoma. (2nd January 2022) - Castillejo Becerra, Clara M.; Dalvin, Lauren A.; Jevremovic, Dragan; Hodge, David O.; Tooley, Andrea A.
ABSTRACT: Purpose: To compare characteristics of initial ocular adnexal (OA) mantle cell lymphoma (MCL) and initial systemic MCL. Methods: Retrospective, comparative case series. Patients treated for MCL at Mayo Clinic from 1/1/1990 to 11/30/2020. MCL was classified as initial OA if first site was OA or initial systemic if first site was elsewhere with progression or recurrence to the OA region. Outcome Measures: Features, treatment, and survival. Results: There were 50 patients with MCL, 23 initial OA and 27 initial systemic. Patients with initial OA MCL had more conjunctival (52% vs. 19%, p = .017) involvement and less frequently received chemotherapy plus autologous stem cell transplant (ASCT) (9% vs. 33%, p = .046) as initial treatment. Complete remission was achieved in 41 (91% vs. 74%, p = .152) patients. Five-year disease-specific survival was similar in initial OA and initial systemic MCL (92% vs. 83%, p = .187). Subanalysis of patients with initial OA MCL revealed 9 (39%) patients developed tumor recurrence, with mean time to recurrence of 28 months. Comparison (no recurrence vs. recurrence) of initial OA MCL patients revealed those with no recurrence had shorter mean final follow-up (3.3 vs. 9.8 years, p = .005) and more frequent initial treatment with rituximab-based chemotherapy plus ASCT (43% vs. 0%, p = .048). Recurrence had no effect on the 5-year age-adjusted risk of death from lymphoma (HR 2.17, 95% CI 0.55–9.09, p = .266). Conclusions: Initial OA and initial systemic MCL patients differ in presentation and management but have similar survival.